2023
DOI: 10.1088/1402-4896/acc6fb
|View full text |Cite
|
Sign up to set email alerts
|

To investigate the structural, electronic, optical and magnetic properties of Sr-doped KNbO3 for perovskite solar cell applications: A DFT study

Abstract: A First-principles study based on density functional theory was conducted to examine the different properties of pure and Sr-doped-KNbO3-perovskites materials such as structural, optical, and electronic properties. The current research was conducted by using CASTEP (Cambridge Serial Total Energy Package) code with USP (Ultra-soft Pseudo-potential) and PBE (Perdew Burke-Ernzerhof) exchange co-relational functional of GGA (Generalized Gradients Approximation). By using a generalized gradient approximation (GGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…An indirect band gap of 0.9 eV is observed at (L-X) symmetry points for RbInBr 3 , as represented in figure 2(b). Upon halide substitution, it is seen that the observed bandgap is enhanced, which is influenced by the electronic states (mostly valence and conduction) of the halide anion that leads to a decrease in electron binding [71]. In addition,…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…An indirect band gap of 0.9 eV is observed at (L-X) symmetry points for RbInBr 3 , as represented in figure 2(b). Upon halide substitution, it is seen that the observed bandgap is enhanced, which is influenced by the electronic states (mostly valence and conduction) of the halide anion that leads to a decrease in electron binding [71]. In addition,…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…For Au- and Ag-doped LNO, Zainuddin et al [ 15 ] calculated a smaller band gap value compared with the pure one. Using the DFT, Jameel et al [ 16 ] showed that Sr-doped KNO is an appropriate material for perovskite solar cell applications. The effect of defects on the spontaneous polarization in pure and doped LNO from first principle calculations were studied by Wang et al [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is a promising candidate for room-temperature multiferroic applications. Density functional theory, using ultra-soft pseudo-potential, was used to study the structural, electronic, magnetic, and optical properties of Sr-doped KNO by Jameel et al [11]. The authors showed that Sr-doped KNO has enhanced band gap, optical conductivity, energy absorption, and refractive index, making it an appropriate material for perovskite solar cell applications.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of theoretical papers that have studied the properties of ion-doped KNO are based on density functional theory [11,13,15]. DFT is a very powerful tool for investigating many-body problems.…”
Section: Introductionmentioning
confidence: 99%